Development of an expert system for the interpretation of serial peak expiratory flow measurements in the diagnosis of occupational asthma. Midlands Thoracic Society Research Group. Issue 11 (1st November 1999) - Burge, P S; Pantin, C F; Newton, D T; Gannon, P F; Bright, P; Belcher, J; McCoach, J; Baldwin, D R; Burge, C B
Abstract : If asthma is due to work exposures there must be a relation between these exposures and the asthma. Asthma causes airway hyperresponsiveness and obstruction; the obstruction can be measured with portable meters, which usually measure peak expiratory flow, or sometimes forced expiratory volume in 1 second (FEV1). These can be measured serially (for instance 2 hourly) over several weeks at and away from work. Once occupational asthma develops, the asthma will be induced by many non-specific triggers common to non-occupational asthma. The challenge is to identify changes in peak expiratory flow due to work among other non-occupational causes. Standard statistical tests have been found to be insensitive or non-specific, principally because of the variable period for deterioration to occur after exposure, and the sometimes prolonged time for recovery to occur, such that days away from work may initially have lower measurements than days at work. A computer assisted diagnostic aid (Oasys) has been developed to separate occupational from non-occupational causes of airflow obstruction. Oasys-2 is based on a discriminant analysis, and achieved a sensitivity of 75% and a specificity of at least 94%; therefore peak expiratory flow monitoring combined with Oasys-2 analysis is better to confirm than to exclude occupational asthma. A neural network version in development has improved on this. Both have been based on expert interpretation of peak flow measurements plotted as daily maximum, mean, and minimum, with the first reading at work taken as the first reading of the day. Oasys has been evaluated with independent criteria against measurements made in a wide range of occupational situations. Oasys is sufficiently developed to be the initial method for the confirmation, although less so for exclusion of occupational asthma.